Does the Locality and Gender of Higher Secondary Students Influence their Life Skills Preferences - Mathur, Madhu; Singh, Swati (JOURNAL OF INDIAN EDUCATION, 2013)
Implicit in the right kind of education is the cultivation of a complete human being with capabilities enhanced in all dimensions: economical, social, cultural, political and ethical. But, unfortunately the learning experiences provided in the formal classroom system are so much devoid of real life situation that the so-called ‘educated’ is rarely competent enough to resolve the intricate real life issues courageously. It requires something more to come out of any crisis in the entire gamut of one’s personal, professional and social life and that vital missing link in the education process is the acquisition of “Life Skills” — capabilities which prepare the learner to cope with life’s diverse challenges. As life skills based education can address a wide range of issues relevant to adolescents, the development of life skills should be the primary concern of secondary education. Life skills are innumerable, so life skills preferences of higher secondary students, if correctly identified would be helpful to get the preliminary idea of those life skills that should be integrated into the existing curriculum of secondary education. Students at higher secondary level are mature enough to express their fair and frank preferences which may prove valuable in the pursuit of quality education. The present paper explores the higher secondary students’ life skills preferences with respect to their locality and gender difference.